Investigations on Joule heating applications by multiphysical continuum simulations in nanoscale systems - Feuchter, Manuel Klaus Ludwig (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2014)
This work furthers the overall understanding of a 3w-measurement, by considering previously unexamined macroscopic influence factors within measurement by Finite Element simulations (FES). Moreover, new measuring configurations are developed to determine (an)isotropic thermal conductivities of nanoscale samples. Since no analytic solutions are available for these configurations, a new evaluation methodology is presented to determine emergent thermal conductivities by FES and Neural Networks.